Exploring undergraduates' perceptions of white board and powerpoint lecture style presentations: A case study in Malaysia - Yee V.C.L.; Sim K.N.; Ng Y.J.; Low L.M.; Chong S.T. (Universiti Putra Malaysia, 2023)
Lecture is a widely used teaching method in universities worldwide as an intellectual discourse for delivering new knowledge. The effectiveness of a lecture depends on the teaching tools used in facilitating the learning process. At the same time, course content plays an important role in determining the effectiveness of a teaching tool. The present paper reports a cross-sectional study on Engineering undergraduates' perception of whiteboard and PowerPoint lecturing in enriching their learning experience. Questionnaires were distributed to 67 Engineering undergraduates. Interviews were conducted with seven Engineering undergraduates and seven lecturers. The survey and interview data collected were subjected to quantitative and content-based analyses, respectively. The findings concluded that whiteboard and PowerPoint lecturing tools complement each other in technical courses. 2017 Universiti Putra Malaysia Press.